Victoria's year : English literature and culture, 1837-1838 - Stein, Richard L. (Oxford University Press, 1987)
A survey of British literature and culture in the first year of Victoria's reign. The discussion ranges over high and low art, literature, painting, architecture, science, the popular press and private memoirs.